Predictors of COVID-19 actual vaccine uptake in Hong Kong: A longitudinal population-based survey. (June 2022) - Yan, Elsie; Lai, Daniel W.L.; Ng, Haze K.L.; Lee, Vincent W.P.
Abstract: Purpose of the research: Identifying predictors of COVID-19 vaccine uptake decisions is central to the development of evidence-based strategies for promoting vaccination. This longitudinal study investigated the link between previous willingness to vaccinate and vaccine uptake decision, and examined potential predictors of vaccine uptake in Hong Kong. Methods: A longitudinal telephone survey study was conducted using a population-based sample of Chinese adult residents (≥18 years) in Hong Kong. Data were collected at two time points: T1 (December 2020–January 2021) and T2 (June–July 2021). Primary outcome was vaccine uptake status; whilst independent variables and covariates included socio-demographic factors, COVID-19 related experiences, health beliefs, and perception, as well as vaccine related perceptions. Results: Among the 1, 003 participants, 23.7% had received a COVID-19 vaccine. Previous willingness to vaccinate did not predict vaccine uptake at later stage. Vaccine uptake by known others ( aOR  = 8.00), trust in authorities ( aOR  = 1.53), acceptability of non-pharmaceutical preventive measures ( aOR  = 2.96), and first-hand experience of COVID-19 ( aOR  = 1.32) were significant predictors of vaccine uptake after adjusting for confounding factors. Conclusions: Future strategies to promote vaccination may focus on building public trust in government and healthcare professional, and encouraging vaccinated individuals to share their vaccine uptake status via social networking. Highlights: Willingness to receive a COVID-19 did not predict later vaccine uptake decision. Vaccine uptake by known others was associated with eightfold odds of vaccine uptake. Trust in authorities in combating COVID-19 predicted vaccine uptake. Campaigns that build public trust in government may help promote vaccination. Encouraging vaccinated individuals to share vaccine status may help motivate others.